Attributes Descriptions among the Medical Lecturers in Implementing the Problem-Based Learning (PBL) Based on the Onion Model Theory - Alya Maharani; Vivi Meidianawaty; Tissa Octavira Permatasari (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2026)
Background: Lecturer attributes influence how Problem-Based Learning (PBL) is facilitated. However, the descriptive profile of lecturer attributes based on the Onion Model has not been previously documented at Faculty of Medicine, Universitas Swadaya Gunung Jati, Cirebon, Indonesia. Understanding these attributes is important to inform faculty development, reflective practice, and curriculum quality improvement. Aims: To describe the attributes of medical lecturers in implementing the PBL based on the Onion Model framework. Methods: This descriptive observational study involved 58 medical lecturers who serve as PBL tutors with varying teaching experience. Participants were selected using purposive sampling and completed the Student-Centred Perspectives on Teaching (SCPT) questionnaire. Responses were measured using a 4-point Likert scale (1 = strongly disagree to 4 = strongly agree). Mean scores above 3 indicate high alignment with student-centred teaching attributes. Data were analysed using univariate descriptive statistics. Results: All Onion Model aspects demonstrated mean scores above 3, indicating generally positive lecturer attributes toward student-centred PBL. The highest mean score was observed in the Belief aspect (3.70), followed by Behaviour and Mission (3.67), Competence (3.56), Environment (3.54), and Identity (3.53). Conclusion: This study provides a descriptive profile of lecturer attributes in PBL implementation. The findings indicate that lecturers generally report student-centred teaching attributes across Onion Model domains. These findings describe lecturer characteristics and do not indicate effectiveness or causal impact on learning outcomes.